Condom-Insistence Conflict in Women's Alcohol-Involved Sexual Encounters With a New Male Partner. (March 2017) - Bryan, Amanda E. B.; Norris, Jeanette; Abdallah, Devon Alisa; Zawacki, Tina; Morrison, Diane M.; George, William H.; Davis, Kelly C.; Danube, Cinnamon L.; Stappenbeck, Cynthia A.
First-time sexual intercourse with a new male partner, relative to other sexual encounters, is associated with heightened risk to women for contracting sexually transmitted infections. Little is known, however, about women's condom-related decision-making processes during these first-time sexual encounters. In the present study, we surveyed a community sample of 179 women aged 18–30 about their alcohol consumption, desire to use a condom, perception of their partner's desire to use a condom, condom-insistence conflict, and condom-decision abdication and use during their most recent alcohol-involved first-time sexual encounter with a new partner. With structural equation modeling, we tested a cognitive mediation model with various configurations of alcohol effects on abdication and condom use (direct, indirect, and moderator). A moderated mediation model fit the data best. Women experienced elevated condom-insistence conflict when they wanted to use a condom and perceived their partner did not; conflict, in turn, was associated with higher likelihood of abdication and lower likelihood of condom use. Higher alcohol intoxication attenuated the associations of desire to use a condom, and perceived partner's desire to use a condom, with conflict. Results support an alcohol myopia-conflict inhibition-reduction model and emphasize the importance of sex education programs that not only teach young women about condom-related assertiveness and the effects of alcohol but also prepare them to respond to experiences of conflict that arise during sexual encounters.